2013
DOI: 10.1016/j.gde.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuned shuttles for bone morphogenetic proteins

Abstract: Bone morphogenetic proteins (BMPs) are potent secreted signaling factors that trigger phosphorylation of Smad transcriptional regulators through receptor complex binding at the cell-surface. Resulting changes in target gene expression impact critical cellular responses during development and tissue homeostasis. BMP activity is tightly regulated in time and space by secreted modulators that control BMPs extracellular distribution and availability for receptor binding. Such extracellular regulation is key for BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 97 publications
0
41
0
Order By: Relevance
“…In the embryo, an orchestra of ligand binding proteins, proteases, and surface proteins are required to form a sharp dorsal stripe of Dpp. In the wing disc, a gradient that scales with the growing tissue requires a network of positive and negative feedback loops [6]. Dpp signaling is also critical for germ cell proliferation and renewal in the ovary and testis.…”
Section: Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the embryo, an orchestra of ligand binding proteins, proteases, and surface proteins are required to form a sharp dorsal stripe of Dpp. In the wing disc, a gradient that scales with the growing tissue requires a network of positive and negative feedback loops [6]. Dpp signaling is also critical for germ cell proliferation and renewal in the ovary and testis.…”
Section: Ligandsmentioning
confidence: 99%
“…Accessory factors have been identified that support ligand-receptor binding, such as the so-called mammalian Type III TGF-β receptor [5]. Several types of “co-receptors” for BMP signaling have been suggested including Dally and Dally-like, two Drosophila glipican homologs, and CV-2, a BMP binding protein that can associate with Punt in some circumstances to facilitate Dpp signaling [6]. The requirement for additional cofactors in Drosophila can also be inferred from contrasting cell culture and in vivo data.…”
Section: Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of twisted gastrulation (Tsg) to BMP‐Sog complexes thereby results in their specific release from collagen IV . By doing so, Tsg enhances Sog/Chordin binding to BMPs and thus enhances BMP mobility, whereas BMP1 family metalloproteases regulate complex disruption by Sog/Chordin cleavage and liberation of bioactive ligands .…”
Section: Regulation Of Bmp Signalingmentioning
confidence: 99%
“…In Drosophila melanogaster embryos, the BMP gradient forms through directed extracellular BMP movement and initiates a positive feedback circuit leading to a bistable pattern of BMP signaling by the end of the blastoderm stage (reviewed in O'Connor et al, 2006; Shilo et al, 2013; Wharton and Serpe, 2013). High levels of BMP signaling, centered on the dorsal midline, specify a single extraembryonic tissue, the amnioserosa.…”
Section: Introductionmentioning
confidence: 99%